Students' Grammatical Errors in Composing English Passive Sentences - Siska Bochari; , Afrillia Anggreni; Maf’ulah Maf’ulah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
Students in learning English grammar often experience difficulties, and are influenced by the first language, namely Indonesian. Students are influenced by the first language, Indonesian, in composing passive sentences and changing active sentences into passive sentences without first identifying the tense used. The students' difficulties in composing passive sentences resulted in difficulties in writing text properly. This is because most students do not understand how to change the active voice to the passive voice, use auxiliary verbs, and identify the tense. The study uses descriptive qualitative method that aims to analyze errors in the preparation of English passive sentences made by the 4th semester students of the English Education Study Program, Tadulako University. In arranging the passive form and which passive form is the most difficult for students to understand and after analyzing the students' mistakes in composing passive sentences, the researchers concluded that of the 50 students who became respondents, the problems that students make in composing passive sentences are 1) changing word order caused by not being able to distinguish between subject and object, 2) not understanding the tense used in active sentences resulting in a change in the auxiliary verb form, 3) reducing or eliminating one of the constituent elements passive, such as the BY preposition, auxiliary verb be, or the suffix –ED to the regular verb. 4) generalizing all passive sentence patterns. Type of error becoming the most dominant thing that students do in making noun clauses is misordering, which is changing the position of the subject and the object without considering the passive patterns and verbs that the sentence has. Next, the passive voice which is the most difficult for students to make is that they had difficulty in constructing passive sentences using the main sentence HAVE or GET followed by a non-finite verb (past participle).